Transformasi Kurikulum Merdeka Belajar Kampus Merdeka Melalui Pendekatan Sosiologi Kritis, Kreativitas Dan Mentalitas Dalam Pembelajaran - Farida Ariani; Firda Khairati Amris; Aulia Fitri; Reflianto Reflianto; Azzahra Vidi Umaira (Institut Agama Islam Sumatera Barat, 2024)
Independent learning curriculum has become an important milestone in the changing higher education system in Indonesia, prompting the need for a thorough transformation to ensure the quality and relevance of education. Critical sociology, creativity, and mentality approaches to learning are considered effective ways to enrich students' learning experiences and prepare them for complex future challenges. This research aims to identify the potential, challenges, and strategies in integrating critical sociology, creativity, and mentality in learning approaches in the transformation of the independent learning curriculum at Universitas Sumatera Barat. In addition, this research also aims to develop a model or practical guide for curriculum developers to adopt the approach in the context of an independent learning curriculum.This research uses a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis. The research respondents consisted of curriculum developers, lecturers, and students at the University of West Sumatra who were involved in the transformation process of the independent learning curriculum. The results of this study show that the integration of critical sociology approaches, creativity, and mentality in learning in the independent learning curriculum at the University of West Sumatra is faced with a number of challenges, such as a lack of understanding of these concepts, limited resources, and resistance to change. However, with the adoption of appropriate strategies, such as training, mentoring, and the development of innovative learning models, the integration of these approaches can be successfully carried out and have a positive impact on students' learning experience.